Archeolodzy uniwersyteccy na Ostrowie Tumskim w Poznaniu - Kóčka-Krenz, Hanna (Folia Praehistorica Posnaniensia, 2013)
The article discusses contribution of archaeologists from the University of Poznań to the study of the origins and development of the early medieval stronghold at Ostrów Tumski, Poznań. The results of their research studies led to the conclusion that the Piasts’ stronghold had been organised on the basis of Carolingian-Ottonian residences with a stone palace and a chapel. These studies also enabled the reconstruction of the further history of the oldest part of Poznań.